NILAI DAN GAYA HIDUP MASYARAKAT DI DALAM MEDIA - Goenawan, Felicia (Scriptura, 2008)
The role of media can be summed up as having the interdependent level in society, especially culture and society’s way of life. In reality, the existences of media depend on society. On of the way to understand its audience is to understand its society. Through lifestyle, media will understand how they can provide things that are acceptable for a society, especially intended and potentially the market target of the media. In the eve of highly forward technology and society development, media is one of human’s need in getting information. But, with the increased amounts of offers from media and their programs, society begins to be selective in choosing the program they watched.